Phenotypic characteristics of the Bonga sheep in Keffa Zone: Field mission Report - Markos, T.; Ginbar, T. (2004)
An investigation was made into the phenotypic characteristics of 192 (168 female and 24 male) Bonga sheep (aged from milk teeth to 4 pairs of permanent incisors) in the Keffa zone using a multi-stage cluster sampling technique to select the sampling units, the households. Based on indicated centre of distribution, the claimed large sheep population size and accessibility, two districts (namely Decha and Chena) were sampled out of the ten districts of the zone. Breed descriptors such as form and appearance, linear body measurements, body weight, scrotal circumference and images of animals were recorded. Adult castrate males with 4 pair of permanent incisors weighed 48 kg, compared to 32 kg for their counterpart ewes. Height at withers for males was 73 cm compared to 64 cm for females. Body length for males with 2 pair of permanent incisors was 69 cm and 63 cm for their female counterparts. Chest girth on the other hand, was 85 cm for males and 72 cm for females. Ear length varied considerably in length (from 4 to 11 cm with mean of 9.8±0.2 cm for females). The Bonga sheep have a characteristic fat-tail, which hangs just above or at the hocks. Tail length was 31 and 41 cm for female and males, respectively. Coat colour is predominantly plain light brown to dark brown (37%), creamy white (9%), and black (5%). As a combination, white with brown, black, or fawn constituted 44% while the combination of brown mainly with white and rarely with black is 39%, and black with white, brown, or fawn was 16%. They had shorthair (range 1.5 to 7.5 cm), some of them having slightly woolly undercoat. The sheep were polled with a slightly convex head profile. Wattle is absent except for 3% of the female sheep. Beard and ruff were absent in both sexes. Scrotal circumference ranged from 22–30 cm. This brief cross-sectional study revealed that the Bonga sheep is slightly different from the Horro by its morphological characteristics, the difference being more distinct in males than in females. A recently proposed study at a molecular genetic characterisation level will hopefully answer some vague areas.